The German adaptation of the Amputee Body Image Scale and the importance of psychosocial adjustment to prosthesis use - Bekrater-Bodmann, Robin (Scientific reports, 2025)
Negative cognitions related to one’s own body, here referred to as body image disturbances (BID), are common after lower limb amputation and correlate with weak psychological functioning. The Amputee Body Image Scale (ABIS) is internationally used to assess BID in persons with lower limb amputation. However, there is no psychometrically evaluated German adaptation available. Including a sample of 191 individuals with lower limb amputation, the present study developed and psychometrically evaluated the German ABIS. Results suggest high reliability in terms of internal consistency and stability of the measure over two years. Meaningful and significant relationships to sex, amputation level, post-amputation pain, mobility, and psychopathology indicate validity of the instrument. Multivariate analyses emphasize a specific and inverse relationship between BID and psychosocial adaptation to the prosthesis including its embodiment. Focussing on ABIS items that are independent of the type of amputation or rehabilitation experiences resulted in an ABIS short form with psychometric properties comparable to the long form. This instrument could be prospectively used in diverse limb loss populations, such as individuals with upper limb amputation or persons not using a prosthesis. The present results thus crucially contribute to the repertoire of patient-reported outcome measures in the context of post-amputation rehabilitation.
Gesehen am 07.07.2025